Без срока давности: роман / К. М. Гурьев - Гурьев Константин Мстиславович (Остросюжет, 2011)
Экземпляры: аб. (2012) / Инвентарный номер: 54024 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Г 95 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44